Screening and application of domestic boron removal resin for ultra-pure water system - TIAN Yuming; XIONG Jianglei; PAN Ting; CHEN Weiyu (Gongye shui chuli)
Boron is one of the key indicators of ultra-pure water quality, which can be removed by boron removal resin, while the resin market is occupied by foreign enterprises. Domestic resin is rarely applied because of unclear operating parameters and instability, which increases the difficulty of promotion. In this study, static adsorption and continuous flow pilot tests of boron removal resin were used to evaluate the performance and project application of typical domestic boron removal resin. According to the multiple evaluation indexes such as adsorption capacity, organic carbon dissolution, regeneration stability, long-term operation stability, procurement cost and supply stability, domestic boron removal resin with excellent performance was selected. The boron adsorption capacity of the domestic boron removal resin could reach 5.1 g/L, TOC dissolution could be as low as 3.01 μg/L, and the boron removal adsorption capacity after 10 times consecutive regeneration was 97.84% of the new resin. High standard boron removal and stable operation were achieved in the continuous pilot line for 9 months, the boron mass concentration of effluent was stably below 10 ng/L. The selected domestic boron removal resin and operating parameters were applied to practical projects, and stable boron removal was achieved to less than 50 ng/L with long-term stable operation.